PENGARUH VARIABEL MAKROPRUDENSIAL DAN MONETER TERHADAP HARGA PROPERTI DI INDONESIA - Apri Yunita; Hasdi Aimon; Dewi Zaini Putri (Universitas Negeri Padang, 2018)
The research aims to see the impact as simultaneous and partial of Loan To Value (LTV), interest rate, and inflation to property prices in Indonesia. The type of data in studies are time series in quarterly data from first quarterly of 2008 to second quarterly of 2016. By using ordinary least square , estimation results show that LTV and interest rate partially have positive and significant impact on property prices in Indonesia. Meanwhile, inflation has negative but not significant on property prices in Indonesia. The suggestion about the the next research is give additional variables or other indication that have impact to property prices in Indonesia. Furthermore, Banks with property loan should arrange new strategy like reduce down payment or provide installments without down payment to homeless society. So that, the mortage growth can be sustained and speculator financing that causes an increase in property prices can be avoided.